AFRO-AMERICAN IN POST-TRUTH ERA: THE STUDY OF THE NEWS ABOUT GEORGE FLOYD INCIDENT - Kristafani A. Liong, Gabriella; Riyandari, Angelika (Proceedings of English Linguistics and Literature, 2020)
Riots incited by George Floyd's incident are proof that racism still exists in the US. Afro-Americans are still largely viewed as the descendants of slaves and following the completion of the “a fool and a crude person” stigma. This paper focuses on the tensions between Black and White Americans displayed by the news regarding George Floyd's incident and other racism-related incidents. The writer analyzes the tensions in the view of post-truth theory where the existence of racism is often denied by the Americans; the knowledge that racism exists, but they are not comfortable talking about it. A multimodality approach is used in the sense that both text and image in the news are analyzed. The writer identifies and locates relevant information, analyzes the evidence, and then develops and discusses the findings. From the analysis, the writer found that the news indeed presents the embodiment of racism in the U.S. contemporary society.